Measuring cognitive-motor integration to detect prolonged performance declines post-concussion. Issue 11 (25th May 2017) - Sergio, Lauren E; Dalecki, Marc; Hurtubise, Johanna; Brown, Jeffrey; Gorbet, Diana; Hughes, Cindy; Macpherson, Alison
Abstract : Objective: There is a higher risk of re-injury for athletes with concussion history when returning to play, despite being asymptomatic and cleared for activity. One possible explanation is that current return to play assessments test thinking and moving separately, but sport activities often require their concurrent processing (cognitive-motor integration, CMI). The aim of this research is to characterize CMI performance across a range of ages and skill levels following concussion. We hypothesize that there will be CMI impairment, even when cognition and motor action measured separately are deemed recovered, and that impairment level is affected by age and skill level. Methods: 133 participants with concussion history (mix of youth, adolescent, university, and elite athletes) and 130 no-concussion controls (age/sex/skill matched) performed two eye-hand coordination tasks. Participants displaced a cursor from a central to peripheral targets by either sliding their finger on a vertically-oriented touchscreen or with decoupled eye-hand coordination (targets/cursor viewed on vertical screen but finger slid on second horizontal touchscreen with 180° cursor feedback rotation). Results: Children, young adult, and elite athletes with concussion history all had CMI performance deficits in movement planning, timing and execution, despite being asymptomatic and returned to play. Younger and less skilled athletes were more impaired relative to older/elite performers. Conclusions: Cognitive-motor integration tasks are successful in detecting performance post-concussion relative to established assessment tools that test these domains separately. We propose that testing CMI performance, a skill crucial in sport, is important to comprehensively assess function post-concussion and to prevent re-injury. Competing interests: None.